Business-design laboratory: A strategy for innovation (2011)
The contribution of industrial design schools to the development of innovative products is well known around the industrialized world. In Colombia, however, industrial design is a young practice and the market is not yet aware of the importance of design as a factor for innovation. In Colombia, the work of industrial designers is almost unknown and there is also no concrete/direct link to the private sector so as to address the real problems of the industry, improving its competitiveness and recognizing the essential attributes of design in its performance. From the academia we are looking for strategies that help us spread the practice of design and encourage companies to do more research, design and product development so as to better compete in the global market. The Business-Design Laboratory is an initiative, whereby a company provides its facilities to one of our final year students for a period of two weeks.